A Country-of-Origin Perspective on Climate Change Actions: Evidence from France, Morocco, and the United States. Issue 1 (March 2021) - Schill, Marie; Godefroit-Winkel, Delphine; Hughes, Mine Üçok
Country-of-origin (COO) research cites the influence of country-level actions on consumers' attitudes but does not specify how such actions might influence the COO image, particularly in a climate change context. However, various countries adopt different climate change actions, with notable potential implications for products associated with the nations' images; therefore, it is vital to understand the relationship between climate change actions and consumers' attitudes toward their country. This study, which solicits responses from 1, 389 consumers in France, Morocco, and the United States, investigates whether and how climate change actions influence each COO image and consumers' attitudes toward it, which vary with consumers' level of climate change concern. Such climate change actions also exert distinct effects that are moderated by the cultural context. Therefore, this study extends the COO literature to a climate change context and provides relevant implications for policy makers and marketing managers aiming to improve their COO image.